Cyborgs-Human + Machine= the Future Man (International Journal of Engineering and Computer Science, 2014)
Neural control/interfacing/interaction is a powerful means, which can develop a robust bridge between humans and machines. In this paper we emphasize on neural interfacing as an evolving trend in wireless communications by taking into account one of its important application i.e. cyborgs. A cyborg is a cybernetic organism (i.e. an organism that is a self-regulating integration of artificial and natural systems). In the next half of the paper we discuss the operational features of cyborgs.In an attempt to promote greater interaction between humans and computers, companies that develop (cybernetic) robotics technologies participate in a variety of seductive strategies that embody the cyborg discourse. Some of these strategies persuade individuals to concede to particular philosophies, such as the argument that technical artifacts and instrumental reasoning are necessary for effective social development. With the experiments conducted and  proposed  to  be  conducted  in  future  and  in  the process give a brief description of the advantages and  disadvantages of this  technology